PERANCANGAN KOMPOR BERBAHAN BAKAR OLI BEKAS UNTUK PENGERINGAN GARAM INDUSTRI - Kurniawan, Harun; Septiana, Reski; Suryanegara, Lisman; Puspanegara, Dinar; Rayhan, Fajri Ashfi; Caniago, Deosa P (Politeknik Negeri Sriwijaya, Indonesia, 2024)
Salt as a source of important minerals is much needed by society and industry. In the salt-making process, salt must go through a drying phase. Salt drying at the Badan Riset Nasional (BRIN)’s workshop that uses wood pellet as the fuel is considered not optimal because of waste in waiting and processing time. Other alternative fuels are needed to maximize the salt production process, one of which is using used lubricating oil. Utilizing used lubricating oil as fuel for the salt drying process requires the conversion of burner or stove. This research aims to design a stove fueled by used lubricant oil for drying industrial salt. French method is used to design the stove. The stove that has been built iwas compared with wood pellet stove in terms of waiting time to reach the desired salt drying temperature, fuel operational costs, and capacity of the salt produced. The ST-44 steel oil stove with a diameter of 17 cm and a height of 13 cm could reach the drying temperature 15 minutes faster than a wood pellet stove without the need of supervising the feeding process. Daily operational costs for fuel consumption using used lubricating oil were also more economical with 25% more dry salt produced than using a wood pellet stove.